RNA splicing is a key mediator of tumour cell plasticity and a therapeutic vulnerability in colorectal cancer - Adam E. Hall (Nature Communications, 2022)
The influence of mRNA splicing on colon cancer development and progression is unclear. In this study, the authors demonstrate that the SRSF1 splicing factor is essential to sustain the stem cell phenotype of WNT-activated colorectal cancers.